Ekstensifikasi Produksi Lada di Indonesia Kurun Waktu 1971-2015 - Sugiartiningsih Sugiartiningsih (Fakultas Ekonomi dan Bisnis, Universitas Jenderal Achmad Yani, 2021)
Abstract The success of the agricultural sector in Indonesia is highly dependent on the main production factor, namely land area. Pepper production as Indonesia's most important plantation crop to improve people's welfare cannot be separated from the influence of land use owned by farmers. The response of farmers to pepper plants is the main key to being able to take advantage of their land area to increase pepper production in Indonesia. The purpose of this study was to determine the extensification of pepper production in Indonesia in the period 1971-2015. The research model used is descriptive analysis using linear regression. From the calculation results, it is found that there is a unidirectional and significant relationship between land area and pepper production in Indonesia. This statement is in accordance with the production theory that increasing the area of ​​land used for pepper cultivation will increase pepper production in Indonesia. According to the reality, Indonesia from a geographical point of view is the country with the largest land area in addition to the high selling value of pepper, especially in the international market. Thus, the response of farmers who are large enough to plant pepper has made pepper status as the main crop and ultimately increased pepper production in Indonesia and was able to increase the export value of plantation products. Abstrak Kesuksesan sektor pertanian di Indonesia sangat tergantung faktor produksi utama yaitu luas lahan. Produksi lada sebagai tanaman perkebunan terpenting Indonesia dalam upaya meningkatkan kesejahteraan rakyat tidak dapat dilepaskan dari pengaruh penggunaan lahan yang dimiliki petani. Respon petani terhadap tanaman lada menjadi kunci utama untuk dapat memnfaatkan luas lahan yang dimiliki untuk peningkatan produksi lada di Indonesia. Tujuan penelitian ini untuk mengetahui ekstensifikasi produksi lada di Indonesia kurun waktu 1971-2015. Model penelitian yang digunakan adalah analisis deskriptif dengan menggunakan regresi linier. Dari hasil perhitungan diperoleh hasil adanya hubungan searah dan signifikan antara luas lahan dengan produksi lada di Indonesia. Pernyataan tersebut sesuai dengan teori produksi bahwa peningkatan luas lahan yang digunakan untuk penanaman lada akan meningkatkan produksi lada di Indonesia. Sesuai realitas Indonesia dari sisi geografis merupakan negara pemilik luas lahan terbesar disamping juga nilai jual lada yang yang cukup tinggi terutama di pasar internasional. Dengan demikian respon petani yang cukup besar untuk menanam lada telah menjadikan status lada sebagai tanaman utama dan akhirnya meningkatkan produksi lada di Indonesia serta mampu meningkatkan nilai ekspor produk perkebunan.